Improving Psychological Well-Being of Prospective Early Childhood Education Teachers: Module Development Using 4D Model - Ulya Rahmanita; Asiyah Asiyah; Nelly Marhayati; Alimni Alimni; Sahib Khatoon (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
This study aims to develop psychological well-being (PWB) module for prospective Early Childhood Education (ECE) teachers using Thiagarajan 4D Model, namely define, design, development and dissemination. The module was validated by material, design, and language experts, then tested for practicality and effectiveness on 43 ECE students. This study adopted the pre-experimental design with type one group pretest-posttest and the instruments used were validation questionnaire and psychological well-being scale from Ryff. Module was declared valid with average expert and practicality test scores of 96.05%, and 90.12%, respectively. Furthermore, the effectiveness test was carried out using a paired sample t-test and obtained score of .001 (t <.05), showing that module was effective in improving psychological well-being of prospective ECE teachers. This module can be used by prospective ECE teachers to develop psychological well-being and prepared to become professional teachers.